Application of V(z) curve technology and ultrasonic testing of flaw detection in various materials - Lee, Jefferson Zhen Zhong. (2010)
Non Destructive Testing techniques are commonly used in many industrial applications for thickness mapping and flaw detection. This report investigates the use of conventional Ultrasonic Testing A and C scan methods (pulse echo technique)and V(z)technique to determine properties of materials with defects.